Simple algorithm's for the calculation of heat transport problem in plate - Kalis, H.; Kangro, I. (Mathematical Modelling and Analysis, 2001)
The approximations of some heat transport problem in a thin plate are based on the finite volume and conservative averaging methods [1,2]. These procedures allow one to reduce the two dimensional heat transport problem described by a partial differential equation to an initial‐value problem for a system of two ordinary differential equations (ODEs) of the first order or to an initial‐value problem for one ordinary differential equations of the first order with one algebraic equation. Solution of the corresponding problems is obtained by using MAPLE routines “gear”, “mgear” and “lsode”.Paprastas algoritmas šilumos laidumo uždaviniui plokštelėje spręstiSantrauka. Šilumos laidumo uždavinio plonoje plokštelėje aproksimacija pagrįsta baigtinių tūrių ir konservatyviuoju vidurkinimo metodu. Šie metodai leidžia dvimatį šilumos laidumo uždavinį, aprašoma dalinėmis išvestinėmis, suvesti į dviejų pirmos eilės paprastųjų diferencialinių lygčių sistemą arba į vieną pirmos eilės paprastąją diferencialinę lygtį su papildoma algebrine lygtimi. Atitinkami parastųjų diferencialinių lygčių sprendiniai randami naudojant MAPLE paketą.First Published Online: 14 Oct 2010